Pengelolaan Pembelajaran dan Pengembangan Bahan Ajar Pendidikan Agama Islam - Sandy Aulia Rahman; Muhammad Ramli (Madrasah: Jurnal Pendidikan Madrasah, 2024)
Islamic Religious Education (PAI) has a strategic role in shaping the character and spiritual values of students. However, the effectiveness of PAI learning is often hampered by less than optimal learning management, such as the lack of teacher pedagogical competence, low student involvement, and limited relevant teaching materials. This research aims to analyze learning management and development of teaching materials in PAI using the library research method. The research results show that teacher management, which includes recruitment, training and evaluation, is very important in ensuring adequate pedagogical competence. Effective student management supports active involvement in the learning process, so that they can understand the material more easily and develop their potential optimally. A comfortable learning environment, both indoor and outdoor, provides a conducive atmosphere for learning. Apart from that, the development of digital-based teaching materials is a solution to increase accessibility and flexibility in learning. With an integrated approach, the management of learning and teaching materials in PAI can be optimized to increase the effectiveness of the teaching and learning process, while also responding to educational needs in the modern era.